Boundary points of angular type form a set of zero harmonic measure - Gardiner, Stephen J.; Sjödin, Tomas (Annales Fennici Mathematici, 2022)
This note addresses a problem of Dvoretzky concerning the harmonic measure of the set of boundary points of a domain in Euclidean space that are of angular type.